Middle and high school girls’ attitude to science, technology, engineering, and mathematics career interest across grade levels and school types - Balta, Nuri; Japashov, Nursultan; Karimova, Ainur; Agaidarova, Shakhrizat; Abisheva, Sholpan; Potvin, Patrice (Frontiers in Education, 2023)
The aim of this study is to examine Kazakh female students’ interest in STEM professions. A convenient sampling method was used to determine the participants from 10 girls’ schools in Almaty city in Kazakhstan. 522 girls from grades 7th to 11th provided answers to the “STEM Career Interest Survey” which was administered online. Collected data was analyzed to see how girls’ STEM carries interest change according to the type of school and grade level, along with locating the correlations between their interests and their end-term marks in each STEM subject. MANOVA analysis showed that girls’ career interests in different STEM subjects are changing for different school levels across types of schools. Through ANOVA analysis we showed that only girls’ math interest significantly changed across school levels. Post-hoc analyses indicated that seventh level students’ interest in math was statistically higher than eighth and ninth level students. For the school type variable, ANOVA analysis showed that only girls’ technology and engineering interests were significantly different across school types. In other words, girls in Nazarbayev Intellectual Schools (NIS) were significantly more interested in technology and engineering careers than public school girls while for science and mathematics there was no difference between the two types of schools. Additionally, at the 8th and 11th school levels NIS girls have a higher interest in science while at the 10th level public school girls have higher scores. Finally, we detected significant correlations of modest amplitude between girls’ STEM were analyzed rest and their achievement in physics, math, chemistry, and biology. This study will allow supporting teachers and school administrators in their efforts to encourage girls to pursue STEM studies and careers, and we hope it will also help researchers to orient their efforts in providing them with fertile and durable solutions.